Labor Competencies in the Strengthening of Local Government Public Management in Peru: Towards Achieving SDG 16 - Garay Canales, Henry Bernardo (2025)
Objective:The study examines how labor competencies encompass technical knowledge, soft skills, attitudes, and values that are fundamental for the modernization and improvement of local public management. The research aligns with Sustainable Development Goal (SDG) 16, emphasizing effective, accountable, and inclusive institutions.Method:The methodology is a systematic literature review using academic databases such as Scopus, Web of Science, SciELO, and JSTOR, with specific inclusion and exclusion criteria for articles published between 2019 and 2024. Results and Discussion:The results reveal a significant gap between the required competencies and those currently possessed by many Peruvian local government officials, identifying challenges such as a shortage of trained technical cadres, clientelistic practices in hiring, lack of investment in continuous training, difficulties in retaining talent, and weaknesses in competency assessment. Conclusion: The study proposes a framework for implementing competency systems tailored to Peru’s local realities, supporting the design of development programs, recruitment systems, and performance evaluations. It highlights the potential of aligning these initiatives with SDG 16 to enhance institutional effectiveness and public trust. Research Implications:The article suggests future lines of research, including comparative studies and analysis of the impact of technology on competency management in local governments.Keywords:labor competencies, subnational public management, peruvian local governments, human capital development, municipal administration, SDG 16, performance evaluation, Sustainable Development Goals (SDGs).